Thermal and spectroscopic studies on solid Ketoprofen of lighter trivalent lanthanides - Galico, D. A. [UNESP]; Holanda, B. B. [UNESP]; Perpetuo, G. L. [UNESP]; Schnitzler, E.; Treu-Filho, O. [UNESP]; Bannach, Gilbert [UNESP] (Springer, 2012)
Solid-state Ln(L)(3) compounds, where Ln stands for trivalent La, Ce, Pr, Nd, Sm, Eu, and L is ketoprofen have been synthesized. Thermogravimetry (TG), differential thermal analysis (DTA), differential scanning calorimetry (DSC) as well as X-ray diffraction powder (DRX) patterns, Fourier transformed infrared spectroscopy (FTIR), and other methods of analysis were used to study solid Ketoprofen of lighter trivalent lanthanides. The results provided information of the composition, dehydration, coordination mode, structure, thermal behavior, and thermal decomposition. The theoretical and experimental spectroscopic study suggests that the carboxylate group of ketoprofen is coordinate to metals as bidentate bond.
Keywords: Ketoprofen; Thermal behavior; Infrared spectroscopy; Carboxylate coordination